Analysis Of The Effectiveness of National Demonstraions Conducted by the Kerala Agricultural University - Syamala K S (Department of Agricultural Extension, College of Horticulture, 1988)
With a view to study the effectiveness of the National Demonstrations on the behaviour of farmers, the present investigation was undertaken under the title “An analysis of the effectiveness of National Demonstrations Conducted by the Kerala Agricultural University”. Effectiveness was measured in terms of the farmers’ knowing about, attitude towards the adoption of the demonstrated cultivation practices of paddy and their attitude towards the National Demonstration program. The farmers’ perception about the methodology followed in the conduct of the demonstrations and the constraints experienced by the farmer-demonstrations in conducting National Demonstrations were also analysed.